Pengaruh terapi kelompok suportif terhadap tingkat ansietas keluarga dalam merawat anak tunagrahita - Dewi, Erti Ikhtiarini; Hamid, Achir Yani S.; Mustikasari, (Jurnal Keperawatan Soedirman, 2012)
Mental retardation is a special needs child who has a physical or social limitations that need care and responsibilities of all time. Care and responsibility it takes time, effort, and cost quite a bit, and could pose a anxiety to the family, so the need to strengthen support in the form of supportive group therapy. The purpose of this study was to analyze the effect of supportive group therapy toward the anxiety level in the care of children at SLB Banyumas District. This study used a quasi experimental design, pre-post test with control group, which will be compared to family anxiety levels between the intervention group and the control group. The results of the statistical test obtained p value of 0.008 indicating a significant difference in anxiety levels between the family intervention group and the control group after administration of supportive group therapy (p≤: 0.05). Supportive group therapy contributes to improved family functioning psychologically so as to reduce anxiety levels of caring for mental retardation. Recommendations of this study is to establish a parent support group in SLB, composed of families who have children with mental retardation.